2013
DOI: 10.1021/cb300671s
|View full text |Cite
|
Sign up to set email alerts
|

Biological Profile of the Less Lipophilic and Synthetically More Accessible Bryostatin 7 Closely Resembles That of Bryostatin 1

Abstract: The bryostatins are a group of twenty macrolides isolated by Pettit and coworkers from the marine organism Bugula neritina. Bryostatin 1, the flagship member of the family, has been the subject of intense chemical and biological investigations due to its remarkably diverse biological activities, including promising indications as therapy for cancer, Alzheimer’s disease, and HIV. Other bryostatins, however, have attracted far less attention, most probably due to their relatively low natural abundance and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The GFP-PKCε, GFP-PKCδ and GFP-RasGRP3 were expressed in LNCaP cells, which we have extensively used for visualization of PKC translocation, as well as for biological analysis of PKC ligands. 3840 GFP-PKCα was expressed in CHO cells, since PKCα shows only limited translocation in response to phorbol esters in LNCaP cells, presumably reflecting a low basal level of internal calcium, which functions as a co-activator of classic PKC isoforms. 38 Representative images are presented for PKCα, for PKCε, for PKCδ, and for RasGRP3 (Figure 3A, 3C, 3E, and 2F, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GFP-PKCε, GFP-PKCδ and GFP-RasGRP3 were expressed in LNCaP cells, which we have extensively used for visualization of PKC translocation, as well as for biological analysis of PKC ligands. 3840 GFP-PKCα was expressed in CHO cells, since PKCα shows only limited translocation in response to phorbol esters in LNCaP cells, presumably reflecting a low basal level of internal calcium, which functions as a co-activator of classic PKC isoforms. 38 Representative images are presented for PKCα, for PKCε, for PKCδ, and for RasGRP3 (Figure 3A, 3C, 3E, and 2F, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…3840 GFP-PKCα was expressed in CHO cells, since PKCα shows only limited translocation in response to phorbol esters in LNCaP cells, presumably reflecting a low basal level of internal calcium, which functions as a co-activator of classic PKC isoforms. 38 Representative images are presented for PKCα, for PKCε, for PKCδ, and for RasGRP3 (Figure 3A, 3C, 3E, and 2F, respectively). For PKCα and PKCε, which showed substantial differences among ligands, the results were also quantitated as the ratio of membrane/cytoplasmic signal (Figure 3B, 3D, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the C-ring portion of the molecule an acetate ester at C20, as opposed to the natural bryostatin 1 (2E,4E)-octa-2,4-dienoate ester, was chosen. The C20 ester is synthetically more convenient, and through the synthesis of bryostatin 7 (K i = 0.26 nM) 22 and a C20 acetate version of Merle 23 (K i = 0.6 nM) 23 we have shown that this substitution has a minimal effect on PKC binding.…”
Section: Resultsmentioning
confidence: 95%
“…Differences in the extent and effect of the two PKC activators (PMA and Bryostatin) have been reported (Wender et al, 1988;Kedei et al, 2013a;Kedei et al, 2013b). In contrast to PMA, Bryostatins do not have tumour promoting activity, but rather show anti-neoplastic features (Hennings et al, 1987;Nakagawa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%